Discrepant involvement of homologous repair and non-homologous end joining pathways in maize development and growth - Shuanghui Zhao; Leiming Zheng; Minghui Zheng; Menghan Li; Shuyue Li; Nan Wu; Yan He; Jinghan Liu (Crop Journal)
Chromosomal DNA double-strand breaks (DSBs) are often generated in the genome of all living organisms. To combat DNA damage, organisms have evolved several DSB repair mechanisms, with nonhomologous end-joining (NHEJ) and homologous recombination (HR) being the two most prominent. Although two major pathways have been extensively studied in Arabidopsis, rice and other mammals, the exact functions and differences between the two DSB repair pathways in maize still remain less well understood. Here, we characterized mre11a and rad50, mutants of HR pathway patterns, which showed drastic degradation of the typically persistent embryo and endosperm during kernel development. Loss of MRE11 or RAD50 function led to chromosomal fragments and chromosomal bridges in anaphase. While we also reported that the NHEJ pathway patterns, KU70 and KU80 are associated with developmental growth and genome stability. ku70 and ku80 both displayed an obvious dwarf phenotype. Cytological analysis of the mutants revealed extensive chromosome fragmentation in metaphase and subsequent stages. Loss of KU70/80 function upregulated the expression of genes involved in cell cycle progression and nuclear division. These results provide insights into how NHEJ and HR are mechanistically executed during different plant developmental periods and highlight a competitive and complementary relationship between the NHEJ and HR pathways for DNA double-strand break repair in maize.